Biological Information:New Perspectives - Robert J Marks II (World Scientific Publishing Co., 2013)
In the spring of 2011, a diverse group of scientists gathered at Cornell University to discuss their research into the nature and origin of biological information. This symposium brought together experts in information theory, computer science, numerical simulation, thermodynamics, evolutionary theory, whole organism biology, developmental biology, molecular biology, genetics, physics, biophysics, mathematics, and linguistics. This volume presents new research by those invited to speak at the conference. The contributors to this volume use their wide-ranging expertise in the area of biological information to bring fresh insights into the many explanatory difficulties associated with biological information. These authors raise major challenges to the conventional scientific wisdom, which attempts to explain all biological information exclusively in terms of the standard mutation/selection paradigm. Several clear themes emerged from these research papers: 1) Information is indispensable to our understanding of what life is; 2) Biological information is more than the material structures that embody it; 3) Conventional chemical and evolutionary mechanisms seem insufficient to fully explain the labyrinth of information that is life. By exploring new perspectives on biological information, this volume seeks to expand, encourage, and enrich research into the nature and origin of biological information. Contents: Session One - Information Theory & Biology: Introductory Comments (Robert J Marks II): Biological Information - What is It? (Werner Gitt, Robert Compton and Jorge Fernandez) A General Theory of Information Cost Incurred by Successful Search (William A Dembski, Winston Ewert and Robert J Marks II) Pragmatic Information (John W Oller, Jr) Limits of Chaos and Progress in Evolutionary Dynamics (William F Basener) Tierra: The Character of Adaptation (Winston Ewert, William A Dembski and Robert J Marks II) Multiple Overlapping Genetic Codes Profoundly Reduce the Probability of Beneficial Mutation (George Montañez, Robert J Marks II, Jorge Fernandez and John C Sanford) Entropy, Evolution and Open Systems (Granville Sewell) Information and Thermodynamics in Living Systems (Andy C McIntosh) Session Two - Biological Information and Genetic Theory: Introductory Comments (John C Sanford): Not Junk After All: Non-Protein-Coding DNA Carries Extensive Biological Information (Jonathan Wells) Can Purifying Natural Selection Preserve Biological Information? (Paul Gibson, John R Baumgardner, Wesley H Brewer and John C Sanford) Selection Threshold Severely Constrains Capture of Beneficial Mutations (John C Sanford, John R Baumgardner and Wesley H Brewer) Using Numerical Simulation to Test the "Mutation-Count" Hypothesis (Wesley H Brewer, John R Baumgardner and John C Sanford) Can Synergistic Epistasis Halt Mutation Accumulation? Results from Numerical Simulation (John R Baumgardner, Wesley H Brewer and John C Sanford) Computational Evolution Experiments Reveal a Net Loss of Genetic Information Despite Selection (Chase W Nelson and John C Sanford) Information Loss: Potential for Accelerating Natural Genetic Attenuation of RNA Viruses (Wesley H Brewer, Franzine D Smith and John C Sanford) DNA.EXE: A Sequence Comparison between the Human Genome and Computer Code (Josiah Seaman) Biocybernetics and Biosemiosis (Donald Johnson) Session Three - Theoretical Molecular Biology: Introductory Comments (Michael J Behe): An Ode to the Code: Evidence for Fine-Tuning in the Standard Codon Table (Jed C Macosko and Amanda M Smelser) A New Model of Intracellular Communication Based on Coherent, High-Frequency Vibrations in Biomolecules (L Dent) Getting There First: An Evolutionary Rate Advantage for Adaptive Loss-of-Function Mutations (Michael J Behe) The Membrane Code: A Carrier of Essential Biological Information That is Not Specified by DNA and is Inherited Apart from It (Jonathan Wells) Explaining Metabolic Innovation: Neo-Darwinism Versus Design (Douglas D Axe and Ann K Gauger) Session Four - Biological Information and Self-Organizational Complexity Theory: Introductory Comments (Bruce L Gordon): Evolution Beyond Entailing Law: The Roles of Embodied Information and Self Organization (Stuart Kauffman) Towards a General Biology: Emergence of Life and Information from the Perspective of Complex Systems Dynamics (Bruce H Weber) Readership: Academics, researchers, postgraduates and advanced undergraduates in bioinformatics. Biologists, mathematicians/statisticians, physicists and computer scientists.